2017
DOI: 10.1007/s13157-017-0963-8
|View full text |Cite
|
Sign up to set email alerts
|

Standing Dead Trees are a Conduit for the Atmospheric Flux of CH4 and CO2 from Wetlands

Abstract: In vegetated wetland ecosystems, plants can be a dominant pathway in the atmospheric flux of methane, a potent greenhouse gas. Although the roles of herbaceous vegetation and live woody vegetation in this flux have been established, the role of dead woody vegetation is not yet known. In a restored wetland of North Carolina's coastal plain, static flux chambers were deployed at two heights on standing dead trees to determine if these structures acted as a conduit for methane emissions. Methane fluxes to the atm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 72 publications
(100 reference statements)
5
17
2
Order By: Relevance
“…They were, however, much lower than tropical Amazon floodplain tree CH 4 fluxes that were one to two orders of magnitude higher than our data (Pangala et al ., ). The only other published standing dead tree stem CH 4 emissions (600 μmol m −2 d −1 ), were from a restored coastal freshwater wetland of North Carolina (Carmichael et al ., ), which was similar to our dead stem fluxes (Fig. ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They were, however, much lower than tropical Amazon floodplain tree CH 4 fluxes that were one to two orders of magnitude higher than our data (Pangala et al ., ). The only other published standing dead tree stem CH 4 emissions (600 μmol m −2 d −1 ), were from a restored coastal freshwater wetland of North Carolina (Carmichael et al ., ), which was similar to our dead stem fluxes (Fig. ).…”
Section: Discussionsupporting
confidence: 90%
“…It is conceivable that active rhizosphere O 2 transport near the root/sediment interface may attenuate CH 4 production and accumulation near the root interface, which may help explain the lower CH 4 fluxes from living tree stems. When tree mortality occurs, water is evacuated from the complex internal hydraulic channels within the trees, spanning from the roots to the atmosphere; leaving an array of empty internal cavities that facilitate upward (nonpressurized) diffusive gas transportation (Carmichael et al ., ). It is also plausible that a portion of the CH 4 flux from dead stems originates aboveground due to the chemical degradation of plant tissue (Keppler et al ., ), in situ methanogenesis from organic matter decomposition (Covey et al ., ; Wang et al ., ), or CH 4 from saprotrophic fungi (Mukhin & Voronin, ; Lenhart et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…() demonstrated that transpiration‐driven CH 4 emissions varies with CO 2 concentration, humidity and other variables that affect stomatal conductance. Diffusive transport of soil‐produced CH 4 can continue after tree death, although net CH 4 consumption on standing dead trees has also been observed (Carmichael et al ., ).…”
Section: Tree Emissions Of Soil‐produced Ch4mentioning
confidence: 97%
“…White and Kaplan (2021) estimate that 19,480 km 2 of coastal forested wetlands have transitioned to other habitat types from 1986 to 2016, some of which were ghost forests at some point during the transition. Snags have the potential to transport soil produced CH 4 through the root and plant tissue cells to the atmosphere, but CH 4 emitted could also be produced internally due to decomposition (Carmichael and Smith, 2016;Carmichael et al, 2017). As the climate changes, ghost forests are projected to expand in area (Kirwan and Gedan, 2019), and therefore could emit a substantial amount of greenhouse gases to the local and regional carbon cycle (Martinez and Ardón, 2021).…”
Section: Introductionmentioning
confidence: 99%